Clinical Picture of SARS-Cov-2 Infection in Children in Guanajuato State, Mexico: A Recent Study - Nicolás Padilla-Raygoza; Gilberto Flores-Vargas; Efraín Navarro-Olivos; María de Jesús Gallardo-Luna (Issues and Development in Health Research Vol. 7, 2021)
Aims: To compare the signs and symptoms in COVID-19 and another respiratory virus, among children. Introduction: Coronaviruses belong to the Coronaviridae family in the Nidovirales order. This virus grew more in human airway epithelial cells than tissue culture cells, suggesting the potential for increased infectivity. Study Design: A cross-sectional study was designed based on data from the National Epidemiological Surveillance System of the General Directorate of Epidemiology. Place and Duration of Study: All registries in database of confirmed and discarded cases of COVID-19 from Guanajuato State, Mexico in the period March-July 2020. Methodology: A confirmed case was one with clinical data mainly fever, cough and dyspnea, who had traveled to a country affected by the pandemic or had had contact with a confirmed case, and a positive rRT-PCR test for SARS -CoV-2. The cases discarded were those with the negative rRT-PCR test. The presence of clinical data among those under 18 years of age, of confirmed and discarded cases in the state of Guanajuato, was compared with Z for two proportions and P-value. Results: The sample included 446 confirmed cases and 2,134 discarded cases. The average age of those confirmed was 9.60 /(/pm/) 5.46 years and 8.01 /(/pm/) 5.39 years, among those discarded (P <.05). In both groups, male predominated (P = .91). Fever, myalgia, arthralgia, and conjunctivitis show statistically significant differences between confirmed and discarded cases (P < .05). Conclusion: There are not differences in signs and symptoms in COVID-19 and another respiratory virus. It is concluded that since the characteristics of COVID-19 are like the ones of other viral infections, the diagnosis cannot be made merely based on signs and symptoms.